Integrating Health Professions in Saudi Arabia: A Narrative Review of Nursing, Dentistry, Public Health, and Administrative Collaboration - Althobiti, Hana Mohammed; Almutairi, Naif Ibrahim; Alamri, Abdulaziz Mohammed; Alharbi, Hani Saleh; Al-Harbi, Tariq Rabeh; AL Mutawa, Adeelah Abdullah; Aljasas, Wafa Ali; Almutlaq, Yasir Abdullah; Majrashi, Majed Ahmed Yahya; Alqatifi, Zainab Taher; et al. (Journal of Posthumanism, 2024)
As the cornerstone of a comprehensive, integrated health service delivery strategy, interprofessional collaboration is crucial to advancing Saudi Arabia’s Vision 2030 agenda. Successful teamwork is underpinned by collaborative leadership and, consequently, performs best within a coordinated interprofessional governance framework. For the past decade, the nursing profession has adopted a collaborative approach aligned with national objectives. Interprofessional education and team-based, patient-centred care have become priorities in response to a uniquely high health workforce dependency ratio. Nursing leadership pathways support system-wide integration, while the scope of practice, regulations, and training and continuing professional development curricula are being adapted to enhance necessary competencies and facilitate partnership-based models. Securing a strong collaborative foundation may accelerate similar efforts in dentistry, public health, and health system administration. The profession’s role as a champion of preventive care lends itself to population-based strategies and other high-impact interventions that address leading disease burdens and align with national strategic objectives. Integration of oral healthcare delivery pathways with other health services enables patients to manage multiple needs simultaneously. Support for interprofessional capacity-building initiatives promotes a more systematic response to oral-systemic linkages and population oral health outcomes. Through these routes, a more holistic strategic interprofessional integration framework can emerge that embraces governance, policy, financing, and regulatory considerations alongside service delivery. Such a system-wide view also encourages coordination and pathway collaboration with entire health system administrative leadership entities and other health disciplines, enabling a more cohesive and aligned approach. Further coordinated exploration of interprofessional collaboration is therefore warranted across the health professions. Population health considerations remain fundamental to service integration and the broader interprofessional agenda. Public health functions in health surveillance, prevention, and promotion are essential to achieving optimal health outcomes, and with health services still evolving from a tertiary treatment orientation, additional scope for activity in these areas remains. Strengthening partnerships between public health and other disciplines—including clinical health services—facilitates a more seamless continuum of care while elevating health sector involvement in addressing pressing socio-economic determinants. Health equity, access, and services for marginalized groups also fall within population health and influence priorities for interprofessional collaborative arrangements across the health professions.